Clinical profile of dengue fever infection in patients admitted in tertiary care centre Agroha, Hisar, Haryana, India - Shah, Mohd Younus; Naqash, Mohd Mubarak; Goel, R. K.; Galhan, Deepak; Kumar, Sunil; Chhabra, Vivek; Saini, Abhishek; Jaggal, K. L. (International Journal of Research in Medical Sciences, 2017)
Background: Dengue infections can result in a wide spectrum of disease severity ranging from an influenza-like illness (dengue fever; DF) to the life-threatening dengue hemorrhagic fever (DHF)/dengue shock syndrome (DSS). The study was aimed to compare the clinical profile of all patients diagnosed with dengue viral infection at MAMC. Methods: This retrospective study included 188 patients infected with dengue virus, age 6 years to 70 years. Laboratory and haematological data were included. Results: Peak of infection occurred in October 2015 and least number of cases were recorded in December 2015. Common clinical symptoms were fever, and abdominal pain. Common haematological abnormalities were thrombocytopenia and leucopoenia. All patients survived. There was no case of dengue hemorrhagic fever or dengue shock syndrome. Conclusions: Significant differences in the clinical profile is possibly because of infection with different serotypes of dengue virus (DENV), concurrent/sequential infection of more than one serotype, and differences in host immune responses associated with host genetic variations.